ESTIMATE OF THE GRAIN YIELD OF OATS CULTIVATED UNDER IRRIGATION LEVELS USING CHLOROPHYLL METER - Coelho, Anderson Prates [UNESP]; Leal, Fabio Tiraboschi [UNESP]; Filla, Vinicius Augusto [UNESP]; Dalri, Alexandre Barcellos [UNESP]; Faria, Rogerio Teixeira de [UNESP] (Faema-fac Educacao & Meio Ambiente, 2018)
The use of indirect measures of vegetation in agriculture, associated with models, is an efficient way of estimating crop productivity. The objective of this study was to verify the accuracy of models to estimate the yield of white oats using as indirect variable chlorophyll measures, besides indicating the best phase and leaf for the evaluation. The field experiment was carried out between May and August 2017 at FCAV/Unesp, Jaboticabal, SP. Irrigation depths were 100%, 87%, 60%, 31% and 11% ETc for treatments L5, L4, L3, L2 and L1, respectively. Each treatment had 4 replicates. The chlorophyll reading (FCI) was performed by the Falker chlorophyll meter ClorofiLOG (R) 1030 in the flag and flag-1 leaves, in 5 plants per plot. The regressions were submitted to analysis of variance (Test F) and their accuracy verified by the determination of the coefficient of determination (R-2), square root mean error (RSME) and mean error (ME). Indirect chlorophyll readings show high correlation with white oat yield. The best accuracy for the estimation of oat yield was the evaluation on the flag leaf and the vegetative phase of the crop (R-2 = 0.81; RSME = 509 kg ha(-1); ME = 0.0072 kg ha(-1)).
Keywords: Chlorophyll; FIC; Models